PENGGUNAAN BAHASA PEMROGRAMAN JAVA EDITOR ECLIPSE HELIOS UNTUK APLIKASI ENGLISH CONVERSATION PADA MOBILEPHONE BERBASIS OPERATION SYSTEM ANDROID - Surmayanti Surmayanti (Jurnal Teknologi Informasi dan Pendidikan, 2016)
Les Exis (Excellent International) is a growing business in services in the field of education such as English, and computer courses. Based on the research conducted in Les Exis, the importance of making the application of English Conversation to support or facilitate learning English Conversation. Therefore, the authors try to design an English Conversation applications that can be mounted or installed on mobilphone android based operating system that is now very popular. The research method used was a field study and research libraries. Thus produced an application by using tools such as UML (Undifeied Modeling Language), Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. In making the application of English Conversation author using the Java programming language and SQLite databases. By using the Java programming in making applications English Conversation can produce a good application in learning English.